Pd/δ-MnO2 nanoflower arrays cordierite monolithic catalyst toward toluene and o-xylene combustion - Li, Yongfeng; Liao, Qianyan; Ling, Weizhao; Ye, Fan; Liu, Fangfang; Zhang, Xipeng; He, Jiajun; Cheng, Gao (Frontiers in Chemistry, 2022)
Exploring high-efficiency and stable monolithic structured catalysts is vital for catalytic combustion of volatile organic compounds. Herein, we prepared a series of Pd/δ-MnO2 nanoflower arrays monolithic integrated catalysts (0.01~0.07 wt.% theoretical Pd loading) via the hydrothermal growth of δ-MnO2 nanoflowers onto the honeycomb cordierite, which subsequently served as the carrier for loading the Pd nanoparticles (NPs) through the electroless plating route. Moreover, we characterized the resulting monolithic integrated catalysts in detail and evaluated their catalytic activities for toluene combustion, in comparison to the controlled samples including only Pd NPs loading and the δ-MnO2 nanoflower arrays. Amongst all the monolithic samples, the Pd/δ-MnO2 nanoflower arrays monolithic catalyst with 0.05 wt.% theoretical Pd loading delivered the best catalytic performance, reaching 90 % toluene conversion at 221 ℃ at a gas hourly space velocity (GHSV) of 10,000 h-1. Moreover, this sample displayed superior catalytic activity for o-xylene combustion under a GHSV of 10,000 h-1. The monolithic sample with optimal catalytic activity also displayed excellent catalytic stability after 30 h constant reaction at 210 and 221 ℃.